2015
DOI: 10.1097/bpo.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Gait Patterns in Children With Limb Length Discrepancy

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 14 publications
3
46
0
3
Order By: Relevance
“…For comparison, pain studies have shown between 20 and 60% decreases in weight bearing in rats with unilaterally induced osteoarthritis ( 71 , 79 ). Our results are consistent with experiments that have found changes in gait, muscle exertion, and oxygen consumption with mild (<1–2 cm) limb length inequality in humans ( 24 , 39 41 , 80 , 81 ). Our findings (Figure 4 B) are also consistent with human studies that have shown gait asymmetry increases as the magnitude of limb length inequality increases ( 18 , 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…For comparison, pain studies have shown between 20 and 60% decreases in weight bearing in rats with unilaterally induced osteoarthritis ( 71 , 79 ). Our results are consistent with experiments that have found changes in gait, muscle exertion, and oxygen consumption with mild (<1–2 cm) limb length inequality in humans ( 24 , 39 41 , 80 , 81 ). Our findings (Figure 4 B) are also consistent with human studies that have shown gait asymmetry increases as the magnitude of limb length inequality increases ( 18 , 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…Differences in limb lengths as small as 4% have been shown to cause back pain in adults ( Knutson, 2005 ). Children with >5.5% difference in limb lengths demonstrated gait compensations that would be expected to lead to secondary pathologies later in life ( Aiona et al , 2014 ). Therefore the magnitude of the discrepancy shown here is well greater than what would be expected to result in secondary skeletal problems ( Walsh et al , 2000 ; Aiona et al , 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Children with >5.5% difference in limb lengths demonstrated gait compensations that would be expected to lead to secondary pathologies later in life ( Aiona et al , 2014 ). Therefore the magnitude of the discrepancy shown here is well greater than what would be expected to result in secondary skeletal problems ( Walsh et al , 2000 ; Aiona et al , 2014 ). There was no difference between tibiae length in normal control mice that had not undergone surgery compared with the contralateral limb in mice that had undergone the surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Those authors also reported compensatory strategies involving both the shorter and longer limbs, with the magnitude of compensation proportional to the size of the LLD. Most investigators agree that pelvic obliquity is a common compensatory strategy during gait among patients with LLD 6,[15][16][17][18][19] .…”
Section: Spine Biomechanics During Gait In Patients With Lldmentioning
confidence: 99%